“Antibiotics Can Work as a Contraceptive:” Contraceptive Knowledge and Use Among University Students in Calabar, Nigeria - Asaolu, Ibitola; Kram, Nidal; Ajala, Christopher; Aquaisua, Ememobong; Asaolu, Akinsola; Kato-Lagumbay, Kylie; Abuh, Alice; Bernand, Moses; Ehiri, John (Frontiers in Reproductive Health, 2021)
Introduction: Many sexually active youths who wish to delay pregnancy are not using any form of modern contraceptives. In sub-Saharan Africa, less than 1 in 5 sexually active youth do not use contraceptives. In Nigeria, 48.4% of all sexually active unmarried women have an unmet need for contraception. Although the literature is replete with information on structural barriers to modern contraceptives, there is limited scholarship on contextual factors that may inhibit modern contraceptive use among Nigerian youth. This study uses a qualitative research approach to assess knowledge and use of natural, modern, and folkloric contraceptive methods among a sample of university students in Calabar, Nigeria. Methods: This study used data from focus group discussions among women and men in university halls of residence, all of whom were unmarried. Also, three male pharmacists and three female community health workers were interviewed. All focus group discussions and interviews took place in August 2017 and were conducted in Calabar Metropolis, Cross River State, Nigeria. The audio recordings were transcribed into detailed summaries of the interviews and focus group discussions. All data analysis was completed using Atlas.Ti (version 8). Results: University men and women have limited knowledge of and application of natural and modern contraception. Participants listed folkloric methods of contraceptives, including repurposing pharmaceuticals (e.g., antibiotics, quinine, and Andrews Livers Salt-a laxative) as contraceptive agents. Respondents also discussed the use of non-pharmaceuticals such as water, salt solution, and squatting after intercourse as contraceptives. Generally, university students defaulted to withdrawal, calendar method, and emergency contraceptives as preferred methods of contraception. Lastly, condoms were used among participants in causal sexual encounters. In dating relationships, however, both male and female students cited their partners' hesitancy to condom use as such act could indicate distrust. Conclusion: Awareness and use of modern contraceptives are limited among university students in Calabar, Nigeria. The use of folkloric contraceptives could lead to bodily harm and unintended pregnancy. Further research is needed to elucidate factors that promote use of folkloric methods of contraceptives. Integration of contraceptive awareness into health promotion services for young people may help to dispel myths about folkloric methods of contraceptives while promoting awareness and use of safe and effective contraception.